2000
DOI: 10.1080/088800100276659
|View full text |Cite
|
Sign up to set email alerts
|

Dna Content and Proliferative Activity in Children With Neuroblastoma

Abstract: Many studies have reported that neuroblastoma patients with aneuploid DNA content and a low cellular proliferative activity have better outcome; other studies have reported contradictory results. Formalin-fixed, paraffin-embedded archival pretreatment specimens of 56 neuroblastomas were studied. Thick sections from paraffin blocks were deparaffinized, and rehydrated. Following enzymatic digestion and filtration, cellular suspensions were analyzed by flow cytometry. Six tumors were aneuploid (13.3%) and 39 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Most of the authors reported only one or two G 0 G 1 peaks in each histogram [3,7,9,10,27]. However, Kusufaka, Yalcin, and Huddart mentioned that samples with a high coefficient of variation (CV>10%) were excluded, considered as having excessive cellular debris.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most of the authors reported only one or two G 0 G 1 peaks in each histogram [3,7,9,10,27]. However, Kusufaka, Yalcin, and Huddart mentioned that samples with a high coefficient of variation (CV>10%) were excluded, considered as having excessive cellular debris.…”
Section: Discussionmentioning
confidence: 94%
“…It is still debated in the literature whether the euploid (di-or tetraploid) tumors have a better outcome in neuroblastoma [17]. Although most authors have reported significant correlation between ploidy and survival rates or the prognostic variables [3,5,7,9,10,23,26], others [4,17,22,27] did not find such an association. In our opinion, the conflicting results in the literature regarding the prognostic utility of ploidy may be explained, in part, by the presence of intratumor DNA content heterogeneity that is difficult to determine, mainly for two reasons.…”
Section: Discussionmentioning
confidence: 95%